2022
DOI: 10.1017/s0031182022000300
|View full text |Cite
|
Sign up to set email alerts
|

Lung flukes of the genusParagonimus: ancient and re-emerging pathogens

Abstract: The title of this article refers to Table 1 in Zhou (2022, Infectious diseases of poverty: progress achieved during the decade gone and perspectives for the future. Infectious Diseases of Poverty 11, 1), in which it is indicated that Paragonimus species, like many other foodborne trematodes, are ancient pathogens that are also re-emerging to cause disease in modern times. This article provides a general overview of Paragonimus species and the disease they cause. This is followed by comments on several specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 82 publications
2
18
0
Order By: Relevance
“…This reflects previous findings based on molecular data, which place these 2 species in a clade with P. macrorchis and P. vietnamensis (e.g. see Blair, 2022). Unfortunately, there is no complete mtDNA sequence for P. s. skrjabini and for other related species, such as P. hokuoensis, P. macrorchis or P. vietnamensis, which could assist in the resolution of the phylogenetic position of P. s. miyazakii and P. s. skrjabini in the Paragonimidae.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This reflects previous findings based on molecular data, which place these 2 species in a clade with P. macrorchis and P. vietnamensis (e.g. see Blair, 2022). Unfortunately, there is no complete mtDNA sequence for P. s. skrjabini and for other related species, such as P. hokuoensis, P. macrorchis or P. vietnamensis, which could assist in the resolution of the phylogenetic position of P. s. miyazakii and P. s. skrjabini in the Paragonimidae.…”
Section: Discussionsupporting
confidence: 90%
“…The separation of Paragonimus species into 2 main groups (the P. westermani complex in one and all remaining species in the other) reflects the pattern seen using other sequence data (e.g. Blair, 2022). Similarly, the P. westermani group itself is subdivided, with the 3 Indian Type 1 mitogenomes being distinct from those from eastern Asia (and rather different from each other).…”
Section: Discussionsupporting
confidence: 69%
“…In the next review article, Blair deals specifically with lung flukes of the genus Paragonimus (Blair, 2022). Here the lung flukes are described as enigmatic parasites that attract less attention than some other neglected tropical diseases.…”
Section: Foodborne Trematodes: the Usual Suspects And New Kids On The...mentioning
confidence: 99%
“…1,2,15,16 Sputum, stool, or biopsies can determine the presence of Paragonimus eggs and distinguish paragonimiasis from other pulmonary diseases of similar presentation (e.g., tuberculosis [TB], cancer, pneumonia, bronchitis, or parapneumonic effusion). 4,5,13,17 As paragonimiasis remains a neglected tropical disease according to the WHO, 18 we sought to review the clinical manifestations, predisposing factors, and treatment of six cases identified in 2017 within the Karan hill-tribe near the Thai-Myanmar border in Umphang District, Tak Province, western Thailand.…”
Section: Introductionmentioning
confidence: 99%